Pertanggungjawaban Hukum Terhadap Perbuatan Melawan Hukum Dalam Tragedi Kanjuruhan Berdasarkan Kitab Undang-Undang Hukum Perdata - Siti Sahnas Dunggio; Weny Almoravid Dungga; Zamroni Abdussamad (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
this study aims to find out about how the legal liability of football competition organizers in the case of unlawful acts in the tragedy of Kanjuruhan Malang in 2022 based on the Civil Code. The method used in this study is normative with legislation and case approach. Legal materials are collected through library studies, then analyzed prescriptively. The results of the study show that the Kanjuruhan tragedy at the Kanjuruhan Stadium in Malang in 2022 has brought losses to many victims so that there is a need for a form of legal accountability regarding unlawful acts committed by the defendant. For this reason, in civil law, the form of liability is in the form of compensation for damages in unlawful acts under Articles 1365, 1367, 1370 and 1371 of the Civil Code committed by the defendant to the victim.